Case report: Low-dose interleukin-2: a treatment of bullous pemphigoid with predominantly perifollicular blistering caused by PD-1/PD-L1 inhibitor - Yingyue Zhang; Yingyue Zhang; Xianwei Cao; Xianwei Cao; Jianbo Tong; Jianbo Tong (Frontiers in Immunology)
ObjectivesThis study aimed to evaluate the efficacy of low-dose interleukin (IL-2) treatment for bullous pemphigoid (BP) caused by anti-programmed cell death protein 1/ligand 1 (PD-1/PD-L1) inhibitors.MethodsLow-dose IL-2 treatment was standardized for BP. The Bullous Pemphigoid Disease Area Index (BPDAI), 5D-Itch Scale (5D-IS), and Dermatology Life Quality Index (DLQI) were recorded before and after treatment, and hexachromatic lymphocytes, regulatory T cells (Treg cells), and cytokines were measured.ResultsA significant decline in the BPDAI score, 5D-IS, and DLQI score was observed following treatment. The count of B-cells, CD4+ T-cells, CD8+ T-cells, Treg cells, and the levels of cytokines (IL-4, -8, and -10) were significantly downregulated in comparison to baseline measurements.ConclusionLow-dose IL-2 could be an effective therapeutic choice for treating BP caused by PD-1/PD-L1 inhibitors.